Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12920-021-01127-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating causal effects of atherogenic lipid-related traits on COVID-19 susceptibility and severity using a two-sample Mendelian randomization approach

Abstract: Background As the number of COVID-19 deaths continues to rise worldwide, the identification of risk factors for the disease is an urgent issue, and it remains controversial whether atherogenic lipid-related traits including serum apolipoprotein B, low-density lipoprotein (LDL)-cholesterol, and triglyceride levels, are risk factors. The aim of this study was to estimate causal effects of lipid-related traits on COVID-19 risk in the European population using a two-sample Mendelian randomization (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Moreover, a study used Mendelian randomization in European population from United Kingdom Biobank to examine the lipid-related traits causal effects on the risk of COVID-19, suggested that higher TG serum level was linked to greater COVID-19 susceptibility (odds ratio (OR) per standard deviation increase in lifelong TG levels, 1.065; 95% CI, 1.001-1.13, p = 0.045), COVID-19 severity (OR, 1.274; 95% CI, 1.08-1.50, p = 0.004), and hospitalization (OR, 1.174; 95% CI, 1.04-1.33, p = 0.012). However, the mechanism that explains the association of hypertriglyceridemia with worsening COVID-19 course is unclear (14). The proposed mechanism for the occurrence of hypertriglyceridemia seems multifaceted (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study used Mendelian randomization in European population from United Kingdom Biobank to examine the lipid-related traits causal effects on the risk of COVID-19, suggested that higher TG serum level was linked to greater COVID-19 susceptibility (odds ratio (OR) per standard deviation increase in lifelong TG levels, 1.065; 95% CI, 1.001-1.13, p = 0.045), COVID-19 severity (OR, 1.274; 95% CI, 1.08-1.50, p = 0.004), and hospitalization (OR, 1.174; 95% CI, 1.04-1.33, p = 0.012). However, the mechanism that explains the association of hypertriglyceridemia with worsening COVID-19 course is unclear (14). The proposed mechanism for the occurrence of hypertriglyceridemia seems multifaceted (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Continued statin use decreases chronic LDL and VLDL-mediated low-grade inflammation seen in obesity, metabolic syndrome, diabetes, heart disease, renal disease, and stroke 27 . Mendelian randomization studies have shown a causal relationship between higher triglyceride levels and increased susceptibility to and severity of COVID-19, suggesting statins could be protective in COVID-19 patients through their lipid-lowering effects 28 . Interestingly, our study revealed lower levels of LDL, VLDL, CRP and hs-CRP, and lower mortality and morbidity outcomes in preexisting statin users compared with nonusers.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study conducted in Milwaukee, WI, during the initial one month of the COVID-19 pandemic (March 1st to March 31st, 2020) reported that people who were enrolled in Medicaid had a higher likelihood of hospital admission [ 48 ]. Other reports also described significant healthcare inequity for Black/African American and Hispanic/Latino communities, which include a disparity in healthcare or insurance access [ 49 ]. Similarly, patients with poorer socioeconomic status were less frequently seek healthcare or only during emergency, which could lead to worsened outcomes during hospitalization [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study conducted during earlier period of the pandemic showed that hypertriglyceridemia during hospitalization in patients with COVID-19 was correlated with mortality [ 12 ], consistent with the findings of the current study. Additionally, based on a genome-wide association study (GWAS), a consistent result was found that genetic variants that associate with hypertriglyceridemia were associated with COVID-19 severity in both inpatients and outpatients [ 49 ]. Likewise, investigation in the genetic variants related to Hemophagocytic lymph histiocytosis, such as the perforin gene, in Asian and non-White Hispanic patients are needed to assess the increased prevalence of hypertriglyceridemia.…”
Section: Discussionmentioning
confidence: 99%